Catastrophic Walrasian Equilibrium from the Non-Walrasian Viewpoint: A Three-Good Macroeconomic Example - Madden, Paul (Review of Economic Studies, 1982)
A Walrasian equilibrium is catastrophic from the non-Walrasian viewpoint if some small deviation from the Walrasian prices produces only non-Walrasian equilibrium allocations a long way from the Walrasian allocation. A precise account of this phenomenon is given for a class of three good, single household private ownership production economies.